Analisis Drug Related Problems (DRPs) Potensial Pada Pasien Geriatri Penderita Osteoporosis di Salah Satu Rumah Sakit Kota Bandung - Yared Yehuda (MEDICINUS, 2025)
Osteoporosis is a skeletal disorder characterized by decreased bone density, which predisposes individuals to an increased risk of fractures of the bones. The prevalence of osteoporosis is quite high among the geriatric patient population. Age-related complex medical problems are common in elderly, making them prone to drug-related problems (DRPs) that can affect therapeutic outcomes. This study aimed to identify and assess the incidence of potential DRPs in geriatric patients with osteoporosis, with or without comorbid condition. A cross-sectional, retrospective study was conducted using secondary data from medical records from January 2018 to December 2020. The sampling method used was purposive sampling, with a total sample of 100 geriatric patients. Inclusion criteria were patients aged >60years, outpatients, diagnosed with osteoporosis with or without comorbid conditions. Exclusion criteria were patients with incomplete or illegible medical record. Classification of DRPs was based on Pharmaceutical Care Network Europe (PCNE) version 9.1. The results showed that there were: drug interaction (43 cases, 39.09%), polypharmacy (29 cases, 26.36%), subtherapeutic doses (9 cases, 8.18%), less frequent drug administration (9 cases, 8.18%), untreated indication (6 cases, 5.45%), drug selection not within guidelines (5 cases, 4.55%), treatment duration too short (5 cases, 4.55%),drug administration without indication (3 cases, 2.73%), and drug duplication (1 case, 0.91%). Total incidence of DRPs was 58%. The most common drug for DRPs is calcium (48,30 %). A multivariate analysis using logistic regression showsthat the number of drugs could significantly affect the incidence of DRPs in patients (p<0.05) by 10.63 times.